Case report: An adult intussusception caused by ascending colon cancer - Zhao, Guowei; Meng, Wenjun; Bai, Lian; Li, Qigang (Frontiers in Surgery, 2022)
Adults with bowel intussusception caused by malignant tumors are fairly uncommon. We presented a case of 64-year-old woman whose intussusception was secondary to ascending colon cancer. A color Doppler ultrasonography of the abdomen revealed a low echo mass in the right middle abdomen. Physical examination and digital rectal examination were both unremarkable. Computed tomography (CT) revealed a concentric circle change in the colon, as well as the mesenterium and arteries. Electronic colonoscopy discovered the colonic giant proliferative lesions and stenosis. Adenocarcinoma with moderate differentiation was discovered after a biopsy. Then laparotomy showed intussusception and the tumor was located in the ascending colon. Postoperative pathological test revealed moderately differentiated adenocarcinoma in the right colon invaded the whole layer. After hospitalization, the patient was discharged without any complication. This case highlights that rational use of CT, endoscopy and timely surgery combines an effective strategy for the treatment of adult intussusception.